Índice de Yang e teoremas generalizados - Costa, Willer Daniel da Silva (2011)
We work with T-spaces (X; T), where X is a Hausdor_ compact space and T : X ! X is a continuous involution without _xed points. Considering the sphere Sn with the antipodal map, we highlight three classical theorems relating to the T-space Sn;A): Borsuk-Ulam's theorem, Kakutani-Yamabe-Yujobô's theorem and Dyson's theorem. This dissertation consists of a detailed study of the article fo C. T. Yang (Annals of Math. 60, no. 2 (1954), 262-282) where the author introduces a concept of the index and presents, in a sense homological, generalizations of the three theorems cited above, considering any T-space. Beyond the generalizations itself, we build examples of the index calculation of some T-spaces and, still, we explore a concept of orthogonality in T-spaces.